2006
DOI: 10.1155/jamds/2006/35752
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high interest rate policy on exchange rates: A reexamination of the Asian financial crisis

Abstract: One of the most controversial issues in the aftermath of the Asian financial crisis has been the appropriate response of monetary policy to a sharp decline in the value of some currencies. In this paper, we empirically examine the effects on Asian exchange rates of sharply higher interest rates during the Asian financial crisis. Taking account of the currency contagion effect, our results indicate that sharply higher interest rates helped to support the exchange rates of South Korea, the Philippines, and Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…(2016) and Bagchi, Chortareas, and Miller (2004) have explained the impact of monetary policy on the changes in value of purchasing power indicators. Moreover, Brailsford et al (2006) also indicate that many Asian countries' exchange rate benefit from the interest rate fluctuation especially during the financial crisis. In addition, Curran and Velic (2019) and Patel and Mah (2018) have found that the monetary policy tools as well as interest rate have a strong causal relationship with the real external purchasing power indicators in the emerging countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2016) and Bagchi, Chortareas, and Miller (2004) have explained the impact of monetary policy on the changes in value of purchasing power indicators. Moreover, Brailsford et al (2006) also indicate that many Asian countries' exchange rate benefit from the interest rate fluctuation especially during the financial crisis. In addition, Curran and Velic (2019) and Patel and Mah (2018) have found that the monetary policy tools as well as interest rate have a strong causal relationship with the real external purchasing power indicators in the emerging countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inflation is one of the effects of a prolonged economic crisis that hit a country. An increase in prices that takes place continuously in an extended period, would be followed by a decline of real value of a country's currency (Brailsford, Jack, & Lai, 2006;Chow & Yoonbai, 2006). Generally, the reason of the economic crisis in Indonesia were not caused by weak economic fundamentals, but because of the declining Rupiah exchange rate against the US Dollar.…”
Section: Introductionmentioning
confidence: 99%